Allochrusa lutea (Caryophylloideae, Caryophyllaceae) a new species from Iran - Mahmoodi, Mohammad; Nejad Falatoury, Atiye (Phytotaxa, 2016)
Allochrusa lutea sp. nov. is here described and illustrated from the Zanjan Province, NW of Iran. A comparison with other Allochrusa species is presented. The more similar species is A. persica from which A. lutea differ by shape of ovary and number of ovules, petals color and the ratio of inflorescence length to stem length. A. lutea is to be considered as endemic to the northern-west of Iran.